FILSAFAT EKONOMI ADAM SMITH - Cuk Ananta Wijaya (Fakultas Filsafat, Universitas Gadjah Mada Yogyakarta, 2009)
AbstractThis essay wants to describe and analyze Adam Smith’s philosophy of Economic. Adam Smith, as the Father of Economics,has really attempted to make economics as a positive-empiricalscience. The science starts and finishes in empirical datas andeliminates theological and speculative explanations. Reality— ultimate reality, is the appearance or empirical reality.Keyword: philosophy of Economic, Adam Smith, a positiveempiricalscience, empirical reality.